Self-efficacy in sport - Feltz, Deborah L.; Short, Sandra E.; Sullivan, Philip Joseph 1969- (Human Kinetics, 2008)
This book provides a reference for sport psychology lecturers, students, coaches and other professionals with an interest in the field. Self-belief, known as 'self-efficacy' by sports psychologists is widely believed to be an essential component of sporting success. This book examines the nature of efficacy as it applies to sporting behaviour in coaches, athletes and teams. It is the first reference book entirely devoted to the concept of self-efficacy in sport. It provides readers with a basic background of research on the topic, as well as current and future trends; offers research-tested guidelines and recommendations for using efficacy techniques with individual athletes and teams; and, includes a comprehensive annotated bibliography of references on the topic